“It feels a bit like drowning”: Expectations and Experiences of Motherhood during COVID-19 - Friedman, May; Kostka Lichtfuss, Kori; Martignetti, Lucas; Gingras, Jacqui (Atlantis)

(untitled) (Mount Saint Vincent University, 2021)
What is the result of bringing unrealistic and overwhelming conditions of motherhood into the context of a global pandemic? This article aims to explore the impacts of maternal expectations and experiences in the context of COVID-19. Through first-person accounts of eighty self-identified mothers parenting through COVID, we aim to explore “good” mother myths, feelings of failure, and the paradoxical freedoms that occur under pandemic time.